Dampak Urbanisasi terhadap Perkembangan Kota di Indonesia: Tinjauan dari Aspek Ekonomi Pembangunan - Dinda Fitria Pida; Khadijah Nur Aini; Cindy Amelia Putri (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
Urbanization is an inevitable phenomenon in many developing countries, including Indonesia, which has experienced rapid growth in recent decades. This study aims to analyze the impact of urbanization on economic development in big cities such as Jakarta, Surabaya, and Bandung. The literature study method is used to collect and analyze various relevant sources. The findings show that although urbanization can drive economic growth and job creation, it also brings significant challenges, such as housing problems, congestion, and pollution. This study concludes that effective management of urbanization requires an integrated and sustainable policy approach. Recommendations for further research and government policies are also presented to support sustainable urban development in Indonesia.